TINJAUAN YURIDIS TERHADAP SENGKETA TANAH DITEPI DANAU TOBA DILIHAT DARI HUKUM ADAT BATAK TOBA - Suyatno, Suyatno; Panda, Daniel; Balantang, Ardito (JOS, 2023)
ABSTRACTIn Simanindo District, Dos Roha Village, Samosir Regency, North Sumatra, in resolving customary land disputes, they still use institutions outside the court. In this area, there are still conflicting interests. The aim of the research is to examine the things that cause customary land disputes. The aim of the research is to examine the things that cause customary land disputes. The role of Traditional Heads in resolving customary land disputes through mediation. Research technique using normative juridical methods, research type through library research. Primary data obtained through secondary data consisting of primary legal materials in the form of legislation The research results show that the things that cause customary land disputes in Simanindo District, Samosisr Regency are unclear customary land boundaries, unfair practices, claims from the State, loss of historical witnesses and perpetrators, wrong understanding of customs, lack of socialization, economic value of land. The role of the traditional head is very important because he can act as a mandate for peace in land dispute. Keywords: Juridical Review, Land Disputes, Toba Batak Customary Law. ABSTRAKDi Kecamatan Simanindo, Desa Dos Roha Kabupaten Samosir Sumatera Utara dalam menyelesaikan sengketa tanah ulayat masih menggunakan Lembaga di luar pengadilan. Di wilayah tersebut masih menimbulkan sengketa kepentingan. Tujuan penelitian untuk menelaah hal-hal yang menyebabkan sengketa tanah ulayat. Peran Kepala Adat dalam penyelesaian sengketa tanah ulayat dengan mediasi. Teknik penelitian dengan metode yuridis normatif jenis penelitian lewat penelitian kepustakaan.Data primer diperoleh melalui data sekunder terdiri dari bahan hukum primer berupa perundang-undangan . Hasil penelitian diperoleh bahwa hal-hal yang yang menyebabkan terjadinya sengketa tanah ulayat di Kecamatan Simanindo,Kabupaten Samosisr adalah batas tanah ulayat tidak jelas ,adanya praktek ketidakadilan,adanya klaim dari Negara ,kehilangan saksi dan pelaku sejarah,pemahaman salah terhadap adat,kurangnya sosialisasi ,nilai tanah secara ekonomi. Peran Kepala adat sangat penting karena bisa sebagai amanat perdamaian dalam sengketa tanah.Kata Kunci : Tinjauan Yuridis,Sengketa Tanah, Hukum Adat Batak Toba.